Dampak Transformasi Tenaga Kerja Pertanian Terhadap Pendapatan Rumah Tangga (Studi Kasus pada Desa Urban dan Ural di Kab. Bogor - Alla Asmara; Tanti Novianti (Jurnal Ilmu Pertanian Indonesia, 2006)
The Objectives of this study are: (1) to identify agricultural household characteristic in rural and urban areas, (2) to identify the factors that encouraging the process of labour transformation in rural and urban areas, and (3) to analyze the process of labour transformation impact to households income in rural and urban. The design of study is the case study in the district of Bogor. The sampling method use multistage sampling with data analyzing of: (1) descriptive analysis, (2) Binary choice model in logistic function, and (3) Income analysis. The results of study show that educational level of head of agricultural household in rural more than urban and conversely for income. The factors in wich influent the decision of head of household to transform in rural are age (X3) and income expectation from non-farm (5). In urban, the factors in which influent decision are self belonging of land (X1), the amount of working age of household family members (X2), the educational level of head of household (X4), and income expectation from non-farm (x5). Income level of houshold in rural and urban is not significant (Prob 0.2906). Mean while, the average of farm income in rural and urban is significant (Prob = 0.0028). The income of transformed farmer is more than pure farmer. The income level significant both rural (Prob = 0.0618) and urban (0.0110).